Preparation method and application of methane-n-hexane co-aromatization catalyst
Through in-situ hydrothermal synthesis of metal-encapsulated ZSM-5 catalyst, NiPt@ZSM-5 catalyst was prepared, which solved the problem of carbon deactivation of existing catalysts at high temperatures and achieved the effect of efficient conversion of methane to aromatic hydrocarbons at low temperatures.
Patent Information
- Application Number
- CN202411793652.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-04
AI Technical Summary
The existing methane oxygen-free aromatization catalysts are rapidly decomposed and deactivated at high temperatures, which limits the development of high-value methane utilization.
The NiPt@ZSM-5 catalyst was prepared by in-situ hydrothermal synthesis method using metal-encapsulated ZSM-5 catalyst. The support Si/Al ratio was 10-100, the platinum loading was 0.1-1 wt.%, and the nickel loading was 1-3 wt.%, which showed excellent catalytic performance in the methane n-hexane coaromassification reaction.
Methane is efficiently converted into aromatic hydrocarbons at lower temperatures (400°C), with high aromatic hydrocarbon selectivity and low carbon deposit selectivity, which significantly improves the stability and reaction efficiency of the catalyst.
Smart Images

Figure CN119746920A_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the application field of preparing aromatic hydrocarbons by catalytic conversion of methane, and in particular to the synthesis and application of a catalyst used for preparing aromatic hydrocarbons by catalytic conversion of methane. Background technology:
[0002] Methane is the most abundant hydrocarbon compound on earth, mainly existing in natural gas, shale gas and natural gas hydrates. In recent years, with the continuous innovation of natural gas, shale gas and other mining technologies, the comprehensive utilization of methane has shown great application prospects. Aromatics, as an important basic chemical raw material, is widely used in the production of synthetic plastics, synthetic fibers, perfumes and other chemicals. In traditional industrial production, aromatics are mainly produced by naphtha reforming. However, with the increasing depletion of petroleum resources and the growing demand for aromatics, it is of great significance to develop a sustainable process for the production of aromatics. Methane oxygen-free aromatization technology can directly convert methane into valuable chemicals such as aromatics and hydrogen, with a reaction atom utilization rate of 100% and high aromatics selectivity. Therefore, methane oxygen-free aromatization has received widespread attention and research.
[0003] In recent years, the methane oxygen-free aromatization catalysts developed at home and abroad mainly use ZSM-5 as a carrier, load metals such as Mo, Zn, and Ga as active components, and introduce second component metals such as Fe, Co, Ni, Ag, Cu, and Y into the catalyst to improve the activity of the catalyst. Sridhara et al. (Appl. Catal. A-Gen., 2020, 589, 117247) studied the effects of the two metal components Ni and Co on the methane oxygen-free aromatization performance of Mo / ZSM-5. The presence of Ni and Co hindered the migration and agglomeration of Mo in the zeolite pores, and enhanced the stability of Mo during the reaction. At the same time, the interaction between Mo and the second component metal changed the activity of Mo and improved the selectivity of benzene. Xu et al. (Appl. Catal. A-Gen., 2020, 589, 117247) synthesized Fe-Mo / ZSM-5 by impregnation. Compared with Mo / ZSM-5, Fe-Mo / ZSM-5 exhibits higher benzene selectivity. In addition, the introduction of Fe causes the coke deposited on the catalyst surface to depolymerize into carbon nanotubes, thereby improving the stability of the catalyst.
[0004] Although the addition of the second component metal can greatly improve the activity and stability of the catalyst, the catalyst will still quickly become carbonized and deactivated due to the high temperature of methane aromatization, which limits the further development of methane aromatization technology. Therefore, developing a catalyst that can activate methane at low temperatures is the key to achieving high-value utilization of methane. Summary of the invention:
[0005] In view of the technical problems in the prior art that the reaction temperature of methane oxygen-free aromatization is too high and the catalyst stability is poor, the present invention provides a method for preparing a methane-n-hexane co-aromatization catalyst. The catalyst has high activity, good stability and high aromatics selectivity, and can achieve high efficient conversion of methane in the methane-n-hexane co-aromatization reaction.
[0006] To achieve the above-mentioned object, the present invention provides a metal-encapsulated ZSM-5 catalyst for methane-n-hexane co-aromatization, wherein the catalyst comprises platinum as an active component and nickel as an auxiliary agent, and exhibits excellent catalytic performance in the methane-n-hexane co-aromatization reaction when the catalyst addition amount is 0.3 g, the reaction temperature is 400° C., and the reaction pressure is 1 MPa, with a n-hexane conversion rate of 95%, a methane conversion rate of 5%, an aromatics selectivity of 81%, and a carbon deposit selectivity of no more than 3%.
[0007] Furthermore, the catalyst carrier is a ZSM-5 molecular sieve, and the Si / Al ratio is 10-100.
[0008] Furthermore, the platinum loading is 0.1-1 wt.%, and the nickel loading is 1-3 wt.%.
[0009] Furthermore, the co-aromatization reaction of the catalyst in the methane-n-hexane system is achieved by the following steps:
[0010] a. Add n-hexane and metal encapsulated ZSM-5 catalyst into a reaction kettle and seal it. The amount of catalyst used is 0.1 g to 1.0 g.
[0011] b. Fill nitrogen into the reactor described in a to replace the air therein with nitrogen, and finally fill it with methane or nitrogen. The reaction temperature is 400-600°C, the reaction pressure is 1-5MPa, and the reaction time is 1-3h.
[0012] c. After the reaction is completed, stop heating, wait for the reactor to cool to room temperature, and collect the liquid product and gas product separately.
[0013] d. The liquid product in step c is filtered to separate the catalyst to obtain the final product, and the n-hexane conversion rate is 85.4% to 100%.
[0014] To achieve the above object, the present invention also provides a method for preparing a metal-encapsulated ZSM-5 catalyst for co-aromatization of methane and n-hexane, comprising the following steps:
[0015] (1) A silicon source, an aluminum source, a metal source, an alkali source, a template, a metal ligand and deionized water are fully mixed to obtain a crystallization solution; the molar ratio of each substance in the crystallization solution is 1.0SiO2:xAl2O3:ySDA:zNa2O:aPt:bNi:cLigand:dH2O, x ranges from 0.05 to 0.005, y ranges from 0.1 to 0.4; z ranges from 0.1 to 0.7; a ranges from 0.001 to 0.01, b ranges from 0.01 to 0.05, and c ranges from 0.033 to 0.18.
[0016] (2) The crystallization liquid is transferred to a hydrothermal synthesis crystallization reactor, the temperature is raised to 150-170° C., and crystallization is performed for 48-72 hours to obtain a solid-liquid mixed product.
[0017] (3) Washing and drying the solid-liquid mixed product obtained in step (2) to obtain a sodium-type metal-encapsulated silicon-aluminum molecular sieve Na-NiPt@ZSM-5.
[0018] (4) The Na-NiPt@ZSM-5 obtained in step (3) is subjected to ion exchange, drying and calcination to obtain a hydrogen-type metal-encapsulated silicon-aluminum molecular sieve H-NiPt@ZSM-5.
[0019] In the present invention, the silicon source is one of silica sol and fumed silica.
[0020] In the present invention, the aluminum source is aluminum isopropoxide.
[0021] In the present invention, the alkali source is sodium metaaluminate.
[0022] In the present invention, the platinum source is platinum nitrate.
[0023] In the present invention, the nickel source is nickel acetate.
[0024] In the present invention, the template agent SDA is tetrapropylammonium hydroxide.
[0025] In the present invention, the metal ligand Ligand is hexadecyl betaine.
[0026] Furthermore, the specific process of preparing the crystallization solution described in step (1) is as follows: adding the calculated amount of platinum nitrate and nickel acetate to 10% deionized water, stirring until completely dissolved, to obtain solution A; taking another 10% deionized water, adding the calculated amount of hexadecyl betaine dropwise, stirring sufficiently, to obtain solution B; under the condition of vigorous stirring, slowly adding solution A dropwise to solution B, stirring sufficiently for 2 hours, to obtain metal complex solution C; then, adding metal ammonia complex solution C to the pre-mixed slurry of silicon source, aluminum source and alkali source; finally, adding the calculated amount of template agent, stirring sufficiently until uniform.
[0027] Furthermore, the specific process of the ion exchange, drying and calcination treatment described in step (3) is as follows: a certain mass of Na-NiPt@ZSM-5 obtained in step (2) is added to a 1 mol / L ammonium chloride solution and stirred, and the mass ratio of Na-NiPt@ZSM-5 to the ammonium chloride solution is 1:30; the temperature is raised to 80°C, stirring is continued for 3 hours, and then washed and dried; the dried product is placed in a muffle furnace, the temperature is first raised to 200°C, calcined in an air atmosphere for 1 to 2 hours, and then raised to 550 to 650°C, and calcined in an air atmosphere for 6 to 10 hours; after repeating the above operation 4 times, it is then reduced at 200 to 400°C in a hydrogen atmosphere for 4 hours to obtain NiPt@ZSM-5.
[0028] Technical effect:
[0029] The metal encapsulated catalyst NiPt@ZSM-5 is prepared by in-situ hydrothermal synthesis. As a common porous acidic catalyst carrier, ZSM-5 has adjustable acidic sites. At the same time, the regular pores and stable pore structure of ZSM-5 can confine the active components to prevent the migration and agglomeration of metal species, significantly improving the performance and stability of the catalytic addition.
[0030] Compared with the prior art, the present invention has the following advantages and progress:
[0031] 1. The operation process of the present invention is simple, the conditions are controllable and the practicability is strong.
[0032] 2. The acidic sites of the prepared NiPt@ZSM-5 catalyst can be adjusted. Due to the framework confinement effect of the molecular sieve, the metal dispersion is high, migration and agglomeration are not easy to occur, and it has high catalytic activity.
[0033] 3. The NiPt@ZSM-5 catalyst has excellent aromatization performance and can directly convert methane into aromatics at a lower temperature. It has high aromatics selectivity and low carbon deposition selectivity, and has good application prospects in the high-value utilization of methane. Description of the drawings:
[0034] Figure 1 The XRD patterns of the catalysts prepared in Example 1 and Comparative Examples 1-3 are shown.
[0035] Figure 2 TEM and particle size distribution diagrams of the catalysts prepared in Example 1 and Comparative Example 3; (ab) Example 1; (cd) Comparative Example 3. Specific implementation method:
[0036] The present invention is described in detail below through specific implementations, which are listed as follows:
[0037] 1. Preparation of metal encapsulated ZSM-5 catalyst
[0038] Example 1
[0039] Fumed silica, aluminum isopropoxide, sodium aluminate, platinum nitrate, nickel acetate, tetrapropylammonium hydroxide, hexadecyl betaine and deionized water are uniformly mixed, and the molar ratio in the mixture is 1.0SiO2:0.02Al2O3:0.1TPAOH:0.105Na2O:0.001Pt:0.01Ni(NO3)2:80H2O:0.033hexadecyl betaine. The preparation method of the crystallization solution is as follows: take 10% of deionized water and mix it with the calculated amount of platinum nitrate and nickel acetate to obtain solution A; weigh another 10% of deionized water and add the calculated amount of hexadecyl betaine, stir it thoroughly to obtain solution B; slowly add solution A to solution B under vigorous stirring, stir it thoroughly for 2 hours, and obtain metal complex solution C; then, add metal ammine complex solution C to the pre-mixed slurry of fumed silica, aluminum isopropoxide and sodium aluminate; finally, add the calculated amount of template agent tetrapropylammonium hydroxide and stir it thoroughly until it is uniform. The crystallization solution is transferred to a hydrothermal synthesis crystallization kettle, the temperature is raised to 170°C, and crystallization is carried out for 72 hours to obtain a solid-liquid mixed product. The obtained solid-liquid mixed product is washed and dried to obtain Na-NiPt@ZSM-5. The obtained Na-NiPt@ZSM-5 was added into a 1 mol / L ammonium chloride solution and stirred, the mass ratio of Na-NiPt@ZSM-5 to the ammonium chloride solution was 1:30; the temperature was raised to 80°C, stirring was continued for 3 hours, and then washed and dried; the dried product was placed in a muffle furnace, the temperature was first raised to 200°C, calcined for 1 hour in an air atmosphere, and then raised to 550°C, calcined for 6 hours in an air atmosphere; the above operation was repeated 4 times, and then reduced at 400°C for 4 hours in a hydrogen atmosphere to obtain NiPt@ZSM-5.
[0040] Comparative Example 1
[0041] Fumed silica, aluminum isopropoxide, sodium aluminate, platinum nitrate, tetrapropylammonium hydroxide, hexadecyl betaine and deionized water are uniformly mixed, and the molar ratio in the mixture is 1.0SiO2:0.02Al2O3:0.1TPAOH:0.105Na2O:0.001Pt:80H2O:0.033hexadecyl betaine. The preparation method of the crystallization solution is as follows: 10% of deionized water is fully mixed with a calculated amount of platinum nitrate to obtain solution A; 10% of deionized water is weighed and added with a calculated amount of hexadecyl betaine, and the solution is fully stirred to obtain solution B; solution A is slowly added dropwise to solution B under vigorous stirring, and the solution is fully stirred for 2 hours to obtain a metal complex solution C; then, the metal ammine complex solution C is added to the pre-mixed slurry of fumed silica, aluminum isopropoxide and sodium aluminate; finally, the calculated amount of template agent tetrapropylammonium hydroxide is added and the mixture is fully stirred until uniform. The crystallization liquid was transferred to a hydrothermal synthesis crystallization reactor, the temperature was raised to 170°C, and crystallization was carried out for 72 hours to obtain a solid-liquid mixed product. The obtained solid-liquid mixed product was washed and dried to obtain Na-Pt@ZSM-5. The obtained Na-Pt@ZSM-5 was added to a 1 mol / L ammonium chloride solution and stirred, and the mass ratio of Na-Pt@ZSM-5 to ammonium chloride solution was 1:30; the temperature was raised to 80°C, and after continuous stirring for 3 hours, it was washed and dried; the dried product was placed in a muffle furnace, the temperature was first raised to 200°C, and calcined in an air atmosphere for 1 hour, and then raised to 550°C, and calcined in an air atmosphere for 6 hours; the above operation was repeated 4 times, and then reduced at 400°C for 4 hours in a hydrogen atmosphere to obtain Pt@ZSM-5.
[0042] Comparative Example 2
[0043] Fumed silica, aluminum isopropoxide, sodium aluminate, nickel acetate, tetrapropylammonium hydroxide, hexadecyl betaine and deionized water are uniformly mixed, and the molar ratio in the mixture is 1.0SiO2:0.02Al2O3:0.1TPAOH:0.105Na2O:0.01Ni:80H2O:0.033hexadecyl betaine. The preparation method of the crystallization solution is as follows: 10% of deionized water is fully mixed with a calculated amount of nickel acetate to obtain solution A; 10% of deionized water is weighed and added with a calculated amount of hexadecyl betaine, and the solution is fully stirred to obtain solution B; solution A is slowly added dropwise to solution B under vigorous stirring, and the solution is fully stirred for 2 hours to obtain a metal complex solution C; then, the metal ammonia complex solution C is added to the pre-mixed slurry of fumed silica, aluminum isopropoxide and sodium aluminate; finally, the calculated amount of template agent tetrapropylammonium hydroxide is added, and the solution is fully stirred until uniform. The crystallization liquid was transferred to a hydrothermal synthesis crystallization reactor, the temperature was raised to 170°C, and crystallization was carried out for 72 hours to obtain a solid-liquid mixed product. The obtained solid-liquid mixed product was washed and dried to obtain Na-Ni@ZSM-5. The obtained Na-Ni@ZSM-5 was added to a 1 mol / L ammonium chloride solution and stirred, and the mass ratio of Na-Ni@ZSM-5 to ammonium chloride solution was 1:30; the temperature was raised to 80°C, and after continuous stirring for 3 hours, it was washed and dried; the dried product was placed in a muffle furnace, the temperature was first raised to 200°C, and calcined in an air atmosphere for 1 hour, and then raised to 550°C, and calcined in an air atmosphere for 6 hours; the above operation was repeated 4 times, and then reduced at 400°C for 4 hours in a hydrogen atmosphere to obtain Ni@ZSM-5.
[0044] Comparative Example 3
[0045] First, the calculated amount of sodium aluminate, aluminum isopropoxide and an appropriate amount of deionized water are uniformly mixed to obtain a clear solution. Then, the calculated amount of tetrapropylammonium hydroxide and fumed silica are sequentially added to the clear solution and stirred thoroughly until uniform. The molar ratio of each substance in the final mixture is 1.0SiO2:0.02Al2O3:0.1TPAOH:0.105Na2O:80H2O. After vigorous stirring for 3 hours, the mixture is placed in a high-pressure hydrothermal autoclave and reacted at 170°C for 3 days. The white solid product is washed with deionized water and dried to obtain Na-ZSM-5. The obtained Na-ZSM-5 is added into a 1 mol / L ammonium chloride solution and stirred, the mass ratio of Na-ZSM-5 to the ammonium chloride solution is 1:30; the temperature is raised to 80°C, stirring is continued for 3 hours, and then washed and dried; the dried product is placed in a muffle furnace, the temperature is raised to 550°C, and calcined in an air atmosphere for 6 hours; the above operation is repeated 3 times to obtain H-ZSM-5.
[0046] The same amount of nickel acetate and platinum nitrate as in Example 1 was added to 50 mL of deionized water and stirred until clear to obtain solution A. The homemade ZSM-5 was added to 50 mL of deionized water and ultrasonically dispersed for 30 minutes to obtain mixture B. Solution A was slowly added dropwise to mixture B. After the addition was completed, the temperature was raised to 80°C and stirred until completely dry. The dried sample was first calcined at 550°C for 6 hours in an air atmosphere, and then reduced at 400°C for 4 hours in a hydrogen atmosphere to obtain NiPt / ZSM-5.
[0047] 2. Application of different catalysts in the co-aromatization of methane and n-hexane
[0048] The catalytic performance test was carried out in a batch reactor with a catalyst loading of 0.3 g. Nitrogen was first charged into the reactor to replace the air therein with nitrogen, and then methane was charged. The reaction pressure was 1 MPa, the reaction temperature was 400 ° C, and the reaction time was 1 h. After the reaction was completed, the heating was stopped, and the reactor was cooled to room temperature, and the liquid product and gas product were collected respectively. The product was analyzed by gas chromatography, and the yield of the product is shown in Table 1. The reaction performance of the metal-encapsulated NiPt@ZSM-5 catalyst is significantly higher than that of the NiPt / ZSM-5 catalyst prepared by the traditional impregnation method. In addition, the performance of the NiPt@ZSM-5 catalyst is also significantly stronger than that of the single metal encapsulated catalyst. NiPt@ZSM-5 showed the best reaction performance in the co-aromatization reaction of methane and n-hexane, with a conversion rate of n-hexane of about 94.5%, a conversion rate of methane of about 5.7%, an aromatics selectivity of 81.3%, and a carbon deposit selectivity of 2.3%.
[0049] Table 1. Reaction results of methane-n-hexane co-aromatization reaction catalyzed by ZSM-5
[0050]
[0051] 3. XRD analysis of different catalysts
[0052] The crystal phase analysis of the samples was performed on a Bruker D8 Advance X-ray diffractometer with a scanning speed of 10° / min and a scanning range of 2θ=5-50°. Figure 1 As shown. The peaks at 7-9° and 23-25° are typical characteristic peaks of ZSM-5, and all samples do not contain obvious impurity peaks, which indicates that the use of molecular sieves to confine metals does not have a significant impact on the skeleton of ZSM-5. In addition, there are no obvious peaks of metal oxides or metal elements in the XRD spectrum, which indicates that the metal is highly dispersed on the surface of ZSM-5.
[0053] 4. TEM analysis of different catalysts
[0054] The morphology of the samples was observed using a Thermo Fisher Talos F200X transmission electron microscope. Figure 2 The average size of metal nanoparticles in NiPt@ZSM-5 is smaller than that in NiPt / ZSM-5, which is only 1.73 nm. This shows that the use of molecular sieves to encapsulate metals can improve the dispersion of active metals on the surface of ZSM-5.
Claims
1. A metal-encapsulated ZSM-5 catalyst for methane-n-hexane co-aromatization, wherein the catalyst uses ZSM-5 as a carrier, a Si / Al ratio of 10 to 100, platinum as an active component, and nickel as an additive. The platinum loading is 0.1 to 1 wt.%, and the nickel metal loading is 1 to 3 wt.%.
2. The metal-encapsulated ZSM-5 catalyst for methane-n-hexane co-aromatization according to claim 1, characterized in that: In the methane-n-hexane co-aromatization system, the reaction temperature is 400-600°C, the reaction pressure is 1-5 MPa, the reaction time is 1-3 h, and the catalyst addition amount is 0.1 g-1.0 g.
3. The metal-encapsulated ZSM-5 catalyst for methane-n-hexane co-aromatization according to claim 1, characterized in that: The preparation method thereof comprises the following steps: (1) fully mixing a silicon source, an aluminum source, a metal source, an alkali source, a template, a metal ligand and deionized water to obtain a crystallization solution; (2) transferring the crystallization liquid to a hydrothermal synthesis crystallization reactor, raising the temperature to 150-170° C., and crystallizing for 48-72 hours to obtain a solid-liquid mixed product; (3) washing and drying the solid-liquid mixed product obtained in step (2) to obtain a sodium-type metal-encapsulated silicon-aluminum molecular sieve Na-Me@ZSM-5; The specific process of preparing the crystallization solution in step (1) is as follows: adding a calculated amount of metal source to 10% deionized water, stirring until completely dissolved, to obtain solution A; taking another 10% deionized water, adding a calculated amount of metal ligand dropwise, stirring sufficiently, to obtain solution B; under vigorous stirring, slowly adding solution A dropwise to solution B, stirring sufficiently for 2 hours, to obtain metal complex solution C; then, adding metal ammonia complex solution C to a pre-mixed slurry of silicon source, aluminum source and alkali source; finally, adding a calculated amount of template agent, stirring sufficiently until uniform; The specific process of the ion exchange, drying and calcination treatment described in step (3) is as follows: a certain mass of Na-Me@ZSM-5 obtained in step (2) is added to a 1 mol / L ammonium chloride solution and stirred, wherein the mass ratio of Na-Me@ZSM-5 to the ammonium chloride solution is 1:30; the temperature is raised to 80°C, stirring is continued for 3 hours, and then washing and drying is performed; the dried product is placed in a muffle furnace, the temperature is first raised to 200°C, calcined in an air atmosphere for 1 to 2 hours, and then raised to 550 to 650°C, and calcined in an air atmosphere for 6 to 10 hours; after repeating the above operation 4 times, the product is reduced at 200 to 400°C in a hydrogen atmosphere for 4 hours to obtain Me@ZSM-5; The molar ratio of silicon source, aluminum source, metal source, alkali source, template, metal ligand and deionized water is 1.0SiO2:x Al2O3:ySDA:z Na2O:a Pt:b Ni:c Ligand:d H2O, x ranges from 0.05 to 0.005, y ranges from 0.1 to 0.4, z ranges from 0.1 to 0.7, a ranges from 0.001 to 0.01, b ranges from 0.01 to 0.05, and c ranges from 0.033 to 0.
18.
4. The metal-encapsulated ZSM-5 catalyst for methane-n-hexane co-aromatization according to claim 3, characterized in that: The silicon source is one of fumed silica or silica sol, the aluminum source is aluminum isopropoxide, the alkali source is sodium aluminate, the platinum source is platinum nitrate, the nickel source is nickel acetate, the template agent is tetrapropylammonium hydroxide, and the metal ligand is hexadecyl betaine.
Citation Information
Cited By
Method for directly preparing diisopropylamine from monoisopropylamine
CN119930442A
A method for the direct preparation of diisopropylamine from monoisopropylamine
CN119930442B